PENGARUH RASIO ALKALI AKTIVATOR DALAM CAMPURAN TANAH-POFA BERDASARKAN UJI TEKAN BEBAS - Muhammad Toyeb; Puspa Ningrum (LPPM Universitas Abdurrab, 2024)
Modern soil stabilization has included environmentally friendly materials in the mixture design. Adding an alkali activator provides an alternative to the innovation of the binder agent for soil stabilization. This study aims to know the effect of adding the alkali activator soluble for soil-POFA mixture on changes in the soil strength characteristic through an unconfined compression test (UCT). The alkali activators are sodium silica (Na2SiO3) and Sodium Hydroxide (NaOH). They prepare with a ratio Si/Al: 1.0, 1.5, 2.0, 2.5, and NaOH concentrated at 10M. Compressive strength to the soil-POFA mixture obtained slightly increased strength, and the soil is clayey sand poorly graded. However, adding the alkali activator increases the soil strength significantly. Thus, the soil-POFA with the alkali activators gained the maximum compressive strength on a ratio of 2.5, and it all has the characteristic of rapid hardening in the initial period as a binder agent.